ANALISIS PPH 21 TERHADAP GAJI KARYAWAN PADA PT. KENCANA UTAMA SEJATI - Desi Desi; Edison Sagala (STIE-PMCI, 2018)
Salaries are strongly associated with taxes. Income earned by employee is always deducted income tax. Not all companies pay income tax with held. There are some companies that only bear half of the income tax, there are also companies that ask their employees to bear their own income tax. Income Tax Clause 21 shall constitute income tax in respect of the work, services and activities carried out by individual taxpayer. The income received in the form of salary, honorarium, allowances and other payments with any name in connection with the work, services or activities undertaken by the taxpayer personally in the country. The amount of Income Tax Clause 21 that must be deducted depends on who the Taxpayer is and what form of income is received and the amount of income received. Method in taking the data is purposive sampling. The data used is data from PT. Kencana Utama Sejati. Methods data analysis used in this study is quantitative methods and Techniques data analysis used is literature study techniques, interview techniques and documentation techniques. The results of this study that many employee status errors that are not updated in accordance with current employee conditions. So that the occurrence of errors in the calculation, the amount reported and the excess in deposting Income Tax Clause 21.Â Key Words: salaries, Income Tax Clause 21, Calculation, reporting, deposit.